(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The effects of adhesive agent on shear stiffness of laminated fabrics bonded with adhesive interlining were investigated. The shear stiffness of face fabrics made of different weave density and adhesive interlinings made of different adhesive condition for mass, number and diameter were measured. As adhesive agent mass increases, shear stiffness values of adhesive interlining and laminated fabric is increased. Furthermore, as weave density of face fabric increases, shear stiffness of face fabrics is increased. The increasing rate (I.R.) of shear stiffness for face fabric by bonding adhesive interlining was obtained from the difference between shear stiffness of laminated fabric and pressed adhesive interlining. The relationship between fixed crossing points of warp and weft by adhesive agents per all crossing points of warp and weft (F.C. (%)), and adhesive agent mass and number was investigated. A prediction method was proposed using the increasing rate (I.R.) and F.C. (%). The predicted shear stiffness of laminated fabric showed good agreements with experimental ones.